Persepsi Mahasiswa Prodi PAI Tentang Pemahaman Ibadah Shalat di UIN Sjech M.Djamil Djambek Bukittinggi - Warlina, Rahmi; Charles, Charles (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research was motivated by the Pai Semester 2 Study Program Students About UnderstandingPrayer Worship at UIN Sjech M. Djamil Djambek Bukittinggi The academic year 2021/2022. Thereare still some students who do not know about the importance of worship for themselves, not a few students who still often neglect to worship Allah SWT, one of which is prayer. This type of research used in this study is quantitative descriptive. The data collection technique used in this study used a questionnaire. The subjects in this research are the 2nd semester PAI Study Program students with a total sample of 38 people. Based on a survey of 38 students regarding Student Perceptions About Understanding Prayer Worship at UIN Sjech M.Djamil Djambek Bukittinggi, statement 1 is 82%,statement 2 is 84%, statement 3 is ‎70%, statement 4 is 76%, statement 5 is is 78%, statement 6 is65%, statement 7 is 38%, statement 8 is 72%, statement 9 is 83% and statement 10 is 82%. It can be seen that the percentage of Student Perception Indicators About Understanding the Worship ofPrayer at UIN Sjech M.‎Djamil Djambek Bukittinggi based on cognitive aspects with an average indicator that is 73% with a range of 61% - 80% is the interpretation of understanding.